Biomechanics of power in sport - Noffal, G. (Strength and Conditioning Journal, 2012)
Success in many athletic and sporting activities may be enhanced by the ability to optimize muscular power output. This article will present the biomechanical definitions, characteristics, and applications of power in sport.